2020
DOI: 10.3390/en13051154
|View full text |Cite
|
Sign up to set email alerts
|

Do Oil and Gas Risk Factors Matter in the Malaysian Oil and Gas Industry? A Fama-MacBeth Two Stage Panel Regression Approach

Abstract: This study examines whether oil and gas risk factors are priced in the returns of Malaysian oil and gas stocks employing asset pricing model with improved version of Fama-MacBeth two-stage panel regression. The findings reveal that oil price risk, gas price risk, and exchange rate risk are priced factors in the returns of oil and gas stocks, alongside market-based risk factors. Oil price, gas price and exchange rate factors are found to be associated with positive risk premium implying that they are systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The findings on the exchange rate risk factor indicate that the stock returns of all sub-industries are positively and differently affected by changes in exchange rate. These findings contribute to extending several important studies of related subject matters (e.g., [3,6,7,9,10,13,15,36]).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The findings on the exchange rate risk factor indicate that the stock returns of all sub-industries are positively and differently affected by changes in exchange rate. These findings contribute to extending several important studies of related subject matters (e.g., [3,6,7,9,10,13,15,36]).…”
Section: Discussionsupporting
confidence: 62%
“…The oil and gas industry has a long value chain and firms within the industry do not operate similar business activities. There are generally several sub-industries in the oil and gas industry [3,18,37]. Therefore, the profit generation process of each sub-industry is not the same, even though all the sub-industries are connected with each other.…”
Section: Literature Support and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al (2017) conducted a study to analyze the relationship between positive or negative market volatility and momentum profits and concluded a negative influence of market volatility on momentum profits. Hoque et al (2020) concluded that the momentum strategy generated negative returns, whereas investors expected high returns from the growth-oriented stock of oil and gas stocks in Malaysia. On the basis of the above literature, we develop the following hypotheses for our study:…”
Section: Review Of Literaturementioning
confidence: 99%
“…This technique suits this research as it deals with both local and temporal data [12]. Panel regression modeling is advantageous over other methodologies in that it increases the amount of information present in the sample, the accuracy of the estimators, and the power of statistical tests [13].…”
Section: Introductionmentioning
confidence: 99%